AN ANALYSIS OF THE RESEARCH PROJECTS AWARDED IN FECIBA USING THE CONSENSUAL ASPECTS OF THE NATURE OF THE SCIENCE - Souza, Flavio Dos Santos; Boss, Sergio Luiz Bragatto [UNESP] (Univ Estadual Sudoeste Bahia, 2023)
The objective of the study is to analyze the research projects awarded at Science Fair Entrepreneurship and Innovation in Bahia (FECIBA) using the consensual aspects of the nature of scientific knowledge. The research carried out was qualitative and document. The data were taken from the two editions of FECIBA magazine and the book Practices to Share (Volume II). The documentary research was analyzed using Bardin's Content Analysis. The result of the research shows that most of the projects developed by students, for science fairs in schools, do not present the problem as a driver of investigative activity.
Keywords: history and philosophy of science; science teaching; science fair